Antithrombogenic properties of Tulbaghia violacea aqueous leaf extracts: assessment of platelet activation and whole blood clotting kinetics. Issue 48 (13th September 2021) - Madike, Lerato N.; Pillay, M.; Popat, Ketul C.
Abstract : Tulbaghia violacea plant extracts have been investigated for their potential therapeutic effects in the management of various ailments, among which are cardiovascular diseases, due to the wide range of phytocompounds that the plant possesses. Abstract : Tulbaghia violacea plant extracts have been investigated for their potential therapeutic effects in the management of various ailments, among which are cardiovascular diseases, due to the wide range of phytocompounds that the plant possesses. One of the major challenges in clinical practice is the inability to control platelet activation and clotting caused by cardiovascular disease interventions. Current treatment methods to inhibit platelet aggregation and thromboxane formation have been associated with major undesirable side effects. This has led to increased research studies on the development of newer and more effective antiplatelet agents. In particular, there has been a growing interest on the potential antiplatelet activity of plant-derived extracts. Hence this study methodically evaluates the anticlotting and antiplatelet properties of T. violacea aqueous leaf extracts. The platelet activity of the plant extracts was assessed using total platelet adhesion, platelet morphology and whole blood clotting kinetics. The 0.1 mg ml −1 T. violacea extract mixed with blood plasma demonstrated the lowest platelet adhesion and activation and also reduced whole blood clotting kinetics. There was a reduction of about 70% in platelet adhesion for the 0.1 mg ml −1 treatment compared to the control in the first 15 min which was supported by morphological characterization under SEM. These observations suggest that T. violacea may be a potential antiplatelet therapeutic agent to inhibit the initial step of platelet adhesion and ultimately reduce the incidence of cardiovascular events.